Features of coronary pathology and its relationship with myocardial fibrosis markers in patients with resistant hypertension - V. A. Lichikaki; V. F. Mordovin; A. Yu. Falkovskaya; I. V. Zyubanova; M. A. Manukyan; E. I. Solonskaya; A. A. Vtorushina; S. A. Khunkhinova; I. A. Skomkina (Российский кардиологический журнал, 2023)
Aim. To evaluate the severity of coronary atherosclerosis and its association with biochemical markers of fibrosis in patients with coronary artery disease (CAD) and resistant hypertension (RHT).Material and methods. The study included 39 patients with CAD and RHT. All patients underwent 24-hour blood pressure (BP) monitoring, office BP numbers were measured. Laboratory diagnostics included routine tests, as well as determination of serum lipocalin, plasma concentration of matrix metalloproteinases 2 and 9 (MMP-2, MMP-9), tissue inhibitor of matrix metalloproteinases-1 (TIMP 1). Coronary atherosclerosis in patients was assessed retrospectively according to medical records with an assessment of the protocols of invasive coronary angiography and multislice computed tomography, performed no more than a year ago from the moment of inclusion in the study with no clinical signs of CAD progression. Obstructive atherosclerosis was considered a coronary artery narrowing by more than 50%.Results. Considering the results of previous coronary angiography, the patients were divided into two groups. In the first group (n=20), coronary artery stenosis was <50%, in the second (n=19) >50% (p<0,05). The compared groups of patients were comparable in sex, age, duration of hypertension, blood pressure level, and the number of antihypertensive drugs taken. There were no differences in blood lipid profile, basal glycemia, uric acid levels, and the frequency of previous cerebral accidents. However, the incidence of diabetes in group 2 was significantly higher (p<0,05). Additionally, there was a significant difference in serum levels of lipocalin and MMP-2 with higher values of these indicators in patients with coronary atherosclerosis stenosis (p=0,02).Conclusion. In patients with RHT with symptoms and signs of myocardial ischemia, the incidence of obstructive coronary atherosclerosis according to coronary angiography is 50%. Diabetes in this category of patients indicates a more frequent obstruction of coronary bed. An increase in the level of MMP-2 and lipocalin in this category of patients is associated with more severe coronary damage and can be considered as an indirect indicator of obstructive coronary atherosclerosis.